2009
DOI: 10.1088/0004-637x/696/1/l48
|View full text |Cite
|
Sign up to set email alerts
|

Non-Gaussian Statistics and Stellar Rotational Velocities of Main-Sequence Field Stars

Abstract: In this Letter, we study the observed distributions of rotational velocity in a sample of more than 16,000 nearby F and G dwarf stars, magnitude complete, and presenting high-precision V sin i measurements. We show that the velocity distributions cannot be fitted by a Maxwellian. In addition, an analysis based on both Tsallis and Kaniadakis power-law statistics is by far the most appropriate statistics and gives a very good fit. It is also shown that single and binary stars have similar rotational distribution… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 14 publications
2
52
0
1
Order By: Relevance
“…(8)), our method allows us to fit any known distribution. In this case, we reach the same conclusion as Carvalho et al (2009), but using a different algorithm, i.e., Tsallis or Kaniadakis distributions are in close agreement to the empirical CDF, although the two distributions show a slight discrepancy in their tails.…”
Section: Application To Main-sequence Field Starssupporting
confidence: 77%
See 3 more Smart Citations
“…(8)), our method allows us to fit any known distribution. In this case, we reach the same conclusion as Carvalho et al (2009), but using a different algorithm, i.e., Tsallis or Kaniadakis distributions are in close agreement to the empirical CDF, although the two distributions show a slight discrepancy in their tails.…”
Section: Application To Main-sequence Field Starssupporting
confidence: 77%
“…On the other hand, Carvalho et al (2009) found a better agreement for two other probability distributions, namely: Tsallis and Kaniadakis. These distributions are based on the concept of maximum entropy.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Kaniadakis statistics has been applied in astrophysics, e.g., relativistic plasmas [19] and stellar rotational velocities [20].…”
Section: Introductionmentioning
confidence: 99%